2016
DOI: 10.1038/onc.2016.304
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in cancer

Abstract: Wnt signaling is one of the key cascades regulating development and stemness, and has also been tightly associated with cancer. The role of Wnt signaling in carcinogenesis has most prominently been described for colorectal cancer, but aberrant Wnt signaling is observed in many more cancer entities. Here, we review current insights into novel components of Wnt pathways and describe their impact on cancer development. Furthermore, we highlight expanding functions of Wnt signaling for both solid and liquid tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
1,890
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,153 publications
(1,936 citation statements)
references
References 204 publications
(216 reference statements)
26
1,890
1
19
Order By: Relevance
“…A better understanding of the mechanisms underlying Wnt signaling therefore might lay the foundation for novel therapeutic approaches. Blocking Wnt secretion with the Porcn inhibitor LGK974 induced regression of multiple tumor models in vivo (Liu et al , 2013) and is currently being investigated in clinical studies (Lum & Chen, 2015; Zhan et al , 2017). Despite the high relevance of secreted Wnt ligands in different cancers and the reported additional Wnt‐independent functions of Porcn (Covey et al , 2012; Erlenhardt et al , 2016), inhibition of Porcn is to date the only pharmacological approach to inhibit Wnt secretion.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the mechanisms underlying Wnt signaling therefore might lay the foundation for novel therapeutic approaches. Blocking Wnt secretion with the Porcn inhibitor LGK974 induced regression of multiple tumor models in vivo (Liu et al , 2013) and is currently being investigated in clinical studies (Lum & Chen, 2015; Zhan et al , 2017). Despite the high relevance of secreted Wnt ligands in different cancers and the reported additional Wnt‐independent functions of Porcn (Covey et al , 2012; Erlenhardt et al , 2016), inhibition of Porcn is to date the only pharmacological approach to inhibit Wnt secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting a soluble Wnt antagonist may increase local Wnt signaling and promote tumor growth. 52 Although Wnt signaling has been shown to stimulate myeloma cell proliferation in vitro, 53 treatment with anti-sclerostin antibody had no effect on myeloma burden in the skeleton or spleen of the 5TGM1-eGFP, 5T2MM, or MM1.S models. The absence of effect across multiple models suggests that sclerostin does not regulate pathways that control tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling promotes tumor growth, 51,52 and aberrant Wnt signaling has been reported to increase myeloma cell proliferation. 53 Soluble Wnt antagonists inhibit endogenous Wnt signaling and therefore the antisclerostin antibody might promote tumor proliferation by stopping Wnt suppression in the local bone microenvironment.…”
Section: Additive Effects Of Anti-sclerostin Antibody and Zamentioning
confidence: 99%
“…Additionally, the β-catenin-independent Wnt pathway has been demonstrated to be upregulated in the CTCs of prostate carcinoma cell lines that demonstrate resistance to androgen receptor inhibition (45). In summary, increasing evidence has revealed that β-catenin-dependent and -independent Wnt signaling may promote tumorigenesis in a tissue-specific manner (46). Furthermore, the proliferation of glioma cells may be inhibited by targeting specific molecules using Wnt2 and β-catenin small interfering RNAs (18,47,48).…”
Section: Discussionmentioning
confidence: 99%